人工智能算力互联互通:生成逻辑、制度梗阻及其分层治理. - 徐浩宇 (Journal of Xi'an Jiaotong University (Social Sciences), 2026)
This article is based on the era context of the "Digital China" strategy and the development of new quality productive forces. It focuses on the institutional challenges emerging in the implementation of China's national strategic initiative of computing power interconnection, such as the inefficiency of computing resource allocation, the ambiguity of stakeholder responsibilities, and the lag in regulatory mechanisms, and conducts systematic institutional research. Against the backdrop of artificial intelligence driving the reconstruction of production factors, the quasi-public nature, high spillover, and cross-domain characteristics of computing power have led to the functional inadequacy of traditional administrative regulation and market allocation models. Therefore, this article adopts an interdisciplinary analytical approach, integrating administrative law theory, the economic theory of public goods. and governance theory, to construct a five-dimensional governance framework covering supply system, stakeholder responsibility. behavioral norms, resource allocation and full-process supervision. The core innovation of this article lies in four breakthroughs. Firstly, it provides a layered governance framework for computing power interconnection, offering theoretical support and institutional references for the future advancement of China's national computing power interconnection initiative. Secondly, it proposes the quasi-public goods positioning of computing power resources. thereby expanding the theoretical boundary of benefit administration in digital infrastructure governance. Thirdly, it designs a dynamic allocation mechanism composed of "national priority projects inclusive quotas-market bidding". aiming to achieve a balanced coordination among security, efficiency, and equity. Fourthly, it reconstructs a full-process regulatory system, advocating the establishment of a governance mechanism of "ex ante classified licensing-interim dynamic supervision-ex post exit assurance". The study further explains the institutional logic of computing power interconnection from three dimensions; building a unified national market, fulfilling the government's duty of benefit administration, and enhancing China's comparative advantage in the global competition for artificial intelligence. It identifies that in practice, computing power interconnection faces problems of regional imbalance. blurred accountability, lack of behavioral norms. inefficient distribution, and regulatory vacuums. To this end, it proposes a layered governance model covering the supply, subject, behavioral, allocation, and regulatory levels. At the macro-level, it emphasizes regional coordination and planning integration; at the meso-level. it clarifies the division of authority and responsibility among governments, enterprises, and industry organizations; and at the micro-level, it improves trading rules and behavioral standards, while institutionalizing the governance of computing power through differentiated allocation mechanisms and a full-process regulatory framework. The conclusion of this article indicates that the essence of computing power interconnection lies in the institutional reconfiguration of digital production factors. Its governance should not only enhance technical interoperability but also improve the institutional supply of regulatory rules through a hierarchical and multi-layered governance model. The policy implications are mainly reflected in constructing a differentiated allocation mechanism of "national priority-inclusive quota market bidding" to optimize the hierarchical scheduling of computing resources, and establishing a full-process regulatory framework of "ex ante classification-dynamic interim supervision-ex post exit assurance" to improve the regulatory system. The academic contribution lies in bridging the gap between legal theory and technological governance by advancing the dual paradigms of "computing power quasi-public-goodsization" and "layered governance". It further constructs a "layered governance framework for computing power" and an "institutional interoperability mechanism". providing a Chinese theoretical contribution and governance model for computing power legislation and global artificial intelligence infrastructure governance.